2001
DOI: 10.1038/ng768
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac malformations, adrenal agenesis, neural crest defects and exencephaly in mice lacking Cited2, a new Tfap2 co-activator

Abstract: The protein EP300 and its paralog CREBBP (CREB-binding protein) are ubiquitously expressed transcriptional co-activators and histone acetyl transferases. The gene EP300 is essential for normal cardiac and neural development, whereas CREBBP is essential for neurulation, hematopoietic differentiation, angiogenesis and skeletal and cardiac development. Mutations in CREBBP cause Rubinstein-Taybi syndrome, which is characterized by mental retardation, skeletal abnormalities and congenital cardiac defects. The CBP/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
334
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(348 citation statements)
references
References 25 publications
14
334
0
Order By: Relevance
“…The normal expression of both Twist and Cart1 in the Gcn5 mutants indicates head mesenchyme forms normally in these mutants. Cranial NTDs have also been reported in Cited2, p300, and CBP mutant embryos (Yao et al, 1998;Oike et al, 1999;Bamforth et al, 2001;Greene and Copp, 2005). Quantitative PCR analyses indicate that Gcn5 is not required for expression of these genes (Fig.…”
Section: Neural Patterning In Gcn5 Flox(neo)/⌬ Mutantsmentioning
confidence: 83%
“…The normal expression of both Twist and Cart1 in the Gcn5 mutants indicates head mesenchyme forms normally in these mutants. Cranial NTDs have also been reported in Cited2, p300, and CBP mutant embryos (Yao et al, 1998;Oike et al, 1999;Bamforth et al, 2001;Greene and Copp, 2005). Quantitative PCR analyses indicate that Gcn5 is not required for expression of these genes (Fig.…”
Section: Neural Patterning In Gcn5 Flox(neo)/⌬ Mutantsmentioning
confidence: 83%
“…CITED2 forms a binary complex with CEBPB that is required to enhance transcriptional activation at numerous promoters. 41,42 For example, gene knockout studies 43 indicate that both CITED2 and CEBPB function as coactivators for the transcription factor AP2. A functional CIT-ED2/CEBPB complex is required for prenatal development, in particular for formation of the neural crest and heart formation.…”
Section: Differentiation-related Genes Specific For Ewsmentioning
confidence: 99%
“…Elevated level of Cited2 then functions to downregulate hypoxia inducible factor (HIF)-1-driven transcription by competing with HIF-1a for binding to CBP/p300 Yin et al, 2002;Freedman et al, 2003). We and others have shown that disruption of the gene encoding Cited2 is embryonic lethal and causes defects in the development of heart and neural tube (Bamforth et al, 2001;Barbera et al, 2002;Yin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%